The Prospects and Legal Security of Investment in Indonesia - Santosa, Jaka; Marthanti, Amas Sari (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The aim of the research is to analyze the prospects for medium- and long-term investment in Indonesia and analyze investment obstacles, especially the legal certainty of investing in Indonesia. The research method used is a descriptive analysis method and uses a normative juridical method. Research data uses secondary data. As a result of the research findings, first, investment prospects in Indonesia have experienced a continuous increase because Indonesia has very abundant resources, it has abundant raw materials and a very large market share as well. Second, to increase investment in Indonesia, the government is very serious about reducing investment barriers, especially providing legal certainty for investment, especially granting investment permits that are simple and have strong legal certainty too.